Polycarbonate resin and polycarbonate resin composition
Patent Information
- Application Number
- JP2020205090
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-11
- Filing Date
- 2020-12-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-12-10
AI Technical Summary
【0014】 本発明のポリカーボネート樹脂は、色相、熱安定性、柔軟性に優れる。また、本発明の ポリカーボネート樹脂組成物は機械的強度や耐熱性に優れる。このようなポリカーボネー ト樹脂やポリカーボネート樹脂組成物を用いることで、高品質の成形品を得ることが可能 となる。本発明のポリカーボネート樹脂やポリカーボネート樹脂組成物は高いバイオマス 度を有する樹脂とすることもでき、高いバイオマス度を有する樹脂材料を普及させること で、持続可能な社会の実現に貢献することができる。
Smart Images

Figure 0007643022000001 
Figure 0007643022000002 
Figure 0007643022000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate resin having excellent color, thermal stability and flexibility, and a polycarbonate resin having excellent mechanical strength and The present invention relates to a polycarbonate resin composition having excellent heat resistance. [Background technology]
[0002] Polycarbonate resins are generally made from bisphenols as monomer components, and are highly transparent, durable, and Taking advantage of its superior thermal resistance and mechanical strength, it is used in electrical and electronic components, automotive parts, optical recording media, It is widely used as an engineering plastic in the optical field, such as lenses. On the other hand, there are concerns about global warming due to the depletion of petroleum resources and increased carbon dioxide emissions. Therefore, the development of carbon-neutral plastics made from plant-derived monomers is being promoted. In this situation, the plant-derived raw material isosorbide (hereinafter A polycarbonate resin made using ISB has been developed. It is beginning to be used in automobile parts, optical applications, and as a replacement for glass (for example, patent (See references 1 and 2).
[0003] Polycarbonate resin obtained from ISB not only has excellent optical properties, but also has Compared to aromatic polycarbonate resins, it has excellent weather resistance and surface hardness. Further improvements in mechanical properties such as tensile elongation and impact resistance in areas where stress is concentrated are required. In response to this problem, for example, Patent Document 3 describes a method for improving impact resistance. It has been developed to improve impact resistance by adding elastomer to polycarbonate resin. As shown. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2004 / 111106 Brochure [Patent Document 2] International Publication No. 2007 / 148604 Brochure [Patent Document 3] JP 2017-88774 A Summary of the Invention [Problem to be solved by the invention]
[0005] As disclosed in Patent Document 3, polycarbonate resin is blended with an elastomer. This is expected to provide excellent impact resistance, but it is often used as an impact improver. The materials used are derived from petroleum and other mainly non-renewable resources. In recent years, the use of non-renewable resources has been increasing. In the midst of this, there are high expectations for a resin that has a higher biomass content and excellent practical properties. is what society demands.
[0006] The object of the present invention is to provide a polycarbonate having excellent color, thermal stability and flexibility. Resin and polycarbonate resin composition using the same, which has excellent impact resistance and heat resistance The purpose is to provide. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the present inventors have discovered a method for producing a soluble ... Using a compound, we have developed a polycarbonate resin that has excellent flexibility, color tone, and thermal stability. Furthermore, by using the polycarbonate resin as an impact resistance improver, We have found a polycarbonate resin composition that has a low biomass content and is excellent in impact resistance and heat resistance. That is, the gist of the present invention is as follows.
[0008] [1] A compound having at least a structural unit represented by formula (1) and a structural unit represented by formula (2): A polycarbonate resin, comprising 10% by weight or more of the structural unit represented by the formula (1), 0% by weight or less, and 30% by weight or more, 80% by weight or more of the structural unit represented by the formula (2) Polycarbonate resin containing
[0009] [ka]
[0010] [ka]
[0011] (In formula (2), n is 2 or more.) [2] The average value of n in the structural unit represented by the formula (2) is 3 or more and 45 or less, [ 1] A polycarbonate resin according to claim 1. [3] 1 The number average molecular weight calculated by H-NMR analysis is 15,000 or more, and 50,000 or less. The polycarbonate resin according to [1] or [2] below. [4] The polycarbonate resin according to any one of [1] to [3] (the first polycarbonate The first polycarbonate resin contains at least a structural unit represented by the formula (1), Polycarbonate resin having a structure different from that of carbonate resin (second polycarbonate resin) A polycarbonate resin composition comprising: The second polycarbonate resin contains 40% by weight or more of the structural unit represented by the formula (1), Contains 90% by weight or less, The weight ratio of the first polycarbonate resin to the second polycarbonate resin is 1 / 99. A polycarbonate resin composition having a viscosity of 1:1 or less. [5] The glass transition temperature of the second polycarbonate resin is 90°C or higher and 200°C or lower. The polycarbonate resin composition according to [4]. [6] The second polycarbonate resin is an aliphatic dihydroxy compound or an alicyclic dihydroxy compound. The polycarbonate according to [4] or [5] contains a structural unit derived from a hydroxy compound. Resin composition. [7] 0. Acrylic resin containing 50% by weight or more of the structural unit represented by the following formula (3). 01% by weight or more and 10% by weight or less of the polyoxyethylene ether according to any one of [4] to [6]. Recarbonate resin composition.
[0012] [ka]
[0013] (In formula (3), R 1 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may have a substituent It is a group. 2 is an aryl group which may have a substituent; It is an alkyl group. [8] Furthermore, polytrimethylene ether glycol having a number average molecular weight of 300 or more and 10,000 or less. Any one of [4] to [7] containing recall at 0.1% by weight or more and 10% by weight or less Item 1. The polycarbonate resin composition according to item 1. [9] A method for producing the polycarbonate resin according to any one of [1] to [3] a dihydroxy compound forming at least a structural unit represented by the formula (1); The dihydroxy compound and the carbonic acid diester which form the structural unit represented by the formula (2) are mono- The process includes a step of subjecting a mer raw material to a polycondensation reaction by an ester exchange reaction, In this step, the dihydroxy compound forming the structural unit represented by the formula (2) is Trimethylene ether glycol, wherein the polytrimethylene ether glycol The number average molecular weight of the polycarbonate resin is 200 or more and 2500 or less. Effect of the Invention
[0014] The polycarbonate resin of the present invention is excellent in color, thermal stability, and flexibility. The polycarbonate resin composition is excellent in mechanical strength and heat resistance. By using polycarbonate resin and polycarbonate resin composition, it is possible to obtain high quality molded products. The polycarbonate resin and polycarbonate resin composition of the present invention have a high biomass content. To popularize resin materials with a high biomass content. This will contribute to the realization of a sustainable society. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below, but the present invention is not limited to the following description. The invention can be modified and implemented in any manner without departing from the spirit and scope of the invention.
[0016] In this specification, when "~" is used to express a numerical value or a physical property value, It will be used including the values before and after it.
[0017] In this specification, the term "repeating structural unit" refers to a structure in which the same structure appears repeatedly in a resin. It means a structural unit that constitutes the resin by linking each other. For example, in the case of polycarbonate resin, the carbonyl group is also called the repeating structural unit. In addition, the term "structural unit" refers to a partial structure that constitutes a resin, and is a repeating structural unit. For example, a specific partial structure sandwiched between adjacent linking groups in a resin. The polymerizable reactive group present in the partial structure or the terminal portion of the polymer and the linking group adjacent to the polymerizable reactive group More specifically, in the case of polycarbonate resin, A carbonyl group is a linking group, and a partial structure sandwiched between adjacent carbonyl groups is called a structural unit. In this specification, the weight ratio of each structural unit in the polycarbonate resin is The total weight of all structural units and linking groups is calculated as 100% by weight.
[0018] [Polycarbonate resin] The first aspect of the present invention is a polymerizable compound having a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2): and a structural unit represented by the formula (1). The structural unit represented by the formula (2) is contained in an amount of 10% by weight or more and 70% by weight or less. The polycarbonate resin contains 80% by weight or more and 80% by weight or less. The structural unit represented by the formula (1) is referred to as "structural unit (1)", and the structural unit represented by the formula (2) is referred to as "structural unit (2)". The structural unit may be referred to as "structural unit (2)". In this case, the polycarbonate resin may be referred to as a "first polycarbonate resin."
[0019] [ka]
[0020] [ka] In formula (2), n is 2 or more.
[0021] The dihydroxy compounds forming the structural unit (1) are stereoisomeric. These include sosorbide (ISB), isomannide, and isoidet. They may be used singly or in combination of two or more. Sorbitol is produced from a variety of starches that are abundant and readily available, and is then dehydrated and condensed. The isosorbide obtained by the process is easily available and can be easily produced, and the properties of the resulting molded products (e.g., durability) are also important. It is the most preferable in terms of heat resistance, impact resistance, surface hardness, and carbon neutrality. From the viewpoint of bone neutrality, it is preferable to use isosorbide.
[0022] The weight ratio of the structural unit (1) in the polycarbonate resin of the present invention is 10% by weight or more, and 70% by weight or more. % by weight or less, and the lower limit is more preferably 15% by weight or more, and further preferably 20% by weight or more. The upper limit is preferably 60% by weight or less, and more preferably 55% by weight or less. % or less, more preferably 50% or less by weight, and particularly preferably 50% or less by weight. The solidification temperature of the carbonate resin can be set to room temperature or higher, and the polycarbonate resin can be pelletized. This prevents the pellets from fusing when they are handled in pellet form. ) The polymer molecular chains containing these compounds form hard segments, resulting in high tensile strength. can be done.
[0023] The dihydroxy compound forming the structural unit (2) is, for example, polytrimethylene ether glycol. PO3G is a 1,3- Use 100% biomass PO3G, synthesized by condensing propanediol. It is preferable that isosorbide or PO3G is produced from plant-derived resources. For example, radiocarbon 14 This can be confirmed by measuring the concentration of C).
[0024] The number average molecular weight of PO3G is preferably 200 or more and 2500 or less. The lower limit is 300 or more. More preferably, the molecular weight is 400 or more, and even more preferably, the molecular weight is 450 or more. The upper limit is 200 More preferably 0 or less, even more preferably 1500 or less, particularly preferably 1200 or less, The most preferable value is 1100 or less. In addition, the average weight of the structural unit (2) in the polycarbonate resin is The degree of overlap (average value of n) is preferably 2 or more and 45 or less. The lower limit is more preferably 5 or more, and more preferably 6 or less. More preferably, the upper limit is 35 or less, and particularly preferably, 7 or more. More preferably, it is 20 or less, particularly preferably 20 or less. When the average degree of polymerization is within the above range, a copolymer containing the structural unit (1) and the structural unit (2) can be obtained. The transparency of the recarbonate is improved. In addition, the polymer molecular chain containing the structural unit (2) The soft segment is formed, and high tensile elongation and excellent impact resistance are exhibited. When polycarbonate resin is used as a modifier and blended with other resins, the resin composition The number average molecular weight of PO3G can be determined by the hydroxyl value described below. Calculated through analysis.
[0025] The weight ratio of the structural unit (2) in the polycarbonate resin of the present invention is 30% by weight or more, and 80% by weight or more. % by weight or less, and the lower limit is more preferably 35% by weight or more, and further preferably 40% by weight or more. The upper limit is preferably 78% by weight or less, and more preferably 75% by weight or less. % or less, more preferably 70% by weight or less, particularly preferably 70% by weight or less. 2) The polymer molecular chains containing these compounds form soft segments, providing high tensile elongation and excellent impact resistance. The polycarbonate resin of the present invention can be used as a modifier to modify other resins. When incorporated, it can improve the impact resistance of the resin composition.
[0026] PO3G is similar to other compounds such as polyethylene glycol (PEG) and polypropylene. Compare with polytetramethylene ether glycol (PPG) and polytetramethylene ether glycol (PTMG) The properties of PO3G are explained in the following form. PEG has good compatibility with the structural unit (1), The copolymer polycarbonate resin of structural unit (1) and PEG is a resin with relatively high transparency. However, because the compatibility is too high, it is difficult to obtain a phase separation morphology that can express elastomeric properties. PEG does not form any polymer, and its tensile elongation and other properties are inferior to those of PO3G. It is easy to become discolored and has poor hue. PO3G has moderate compatibility with structural unit (1). Therefore, the phase consisting of PO3G structural units is uniformly dispersed in micron size. For this reason, PPG has excellent flexibility and impact resistance. However, PPG has the disadvantage of having a relatively low thermal decomposition temperature and poor thermal stability. Since PTMG is not compatible with the structural unit (1), a transparent resin cannot be obtained. However, this causes non-uniform phase separation, resulting in poor flexibility and impact resistance improvement effects. Inferior.
[0027] The polycarbonate resin of the present invention does not contain any structural unit other than the structural unit (1) and the structural unit (2). In the following, structural units other than the structural unit (1) and the structural unit (2) are referred to as "other structural units". Examples of compounds that form other structural units include aliphatic dimers. Hydroxy compounds, alicyclic dihydroxy compounds, ether-containing dihydroxy compounds, acetonitrile compounds, These include tar-containing dihydroxy compounds, aromatic dihydroxy compounds, and diester compounds. In addition, polycarbonates partially incorporating structural units derived from diester compounds are In this specification, the polycarbonate resin is referred to as a polyester carbonate resin. The term "carbonate resin" is intended to include polyester carbonate resin.
[0028] Examples of the aliphatic dihydroxy compound include the following dihydroxy compounds: Ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4 -Butanediol, 1,5-heptanediol, 1,6-hexanediol, 1,9-no Straight-chain aliphatic acids such as nandiol, 1,10-decanediol, and 1,12-dodecanediol Dihydroxy compounds; 1,3-butanediol, 1,2-butanediol, neopentyl Branched chain aliphatic dihydroxy compounds such as glycol and hexylene glycol.
[0029] Examples of the alicyclic dihydroxy compound include the following dihydroxy compounds: 1,2-Cyclohexanedimethanol, 1,3-Cyclohexanedimethanol, 1,4 -Cyclohexanedimethanol, Tricyclodecanedimethanol, Pentacyclopentadecane Candimethanol, 2,6-Decalindimethanol, 1,5-Decalindimethanol, 2 ,3-Decalin dimethanol, 2,3-Norbornane dimethanol, 2,5-Norborna Terpene compounds such as 1,3-adamantanedimethanol, limonene, etc. Dihydroxy compounds derived from alicyclic hydrocarbons are exemplified by primary alcohols of alicyclic hydrocarbons. Dihydroxy compounds; 1,2-cyclohexanediol, 1,4-cyclohexanediol 1,3-Adamantanediol, Hydrogenated Bisphenol A, 2,2,4,4-Tetramethylenediol Alicyclic hydrocarbon secondary alcohols, such as ethyl-1,3-cyclobutanediol, etc. or a dihydroxy compound which is a tertiary alcohol.
[0030] Ether-containing dihydroxy compounds include oxyalkylene glycols and acetals. Examples of oxyalkylene glycols include dihydroxy compounds containing an aryl ring. For example, diethylene glycol, triethylene glycol, tetraethylene glycol Polyethylene glycol, polypropylene glycol, polytetramethylene glycol etc. can be used.
[0031] Examples of acetal-containing dihydroxy compounds include spiroglycol (also known as 3, 9-Bis(1,1-dimethyl-2-hydroxyethyl-2,4,8,10-tetraoxa Spiro[5,5]undecane) and dioxane glycol (also known as 2-(1,1-dimethyl -2-hydroxyethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane etc. can be used.
[0032] As the aromatic dihydroxy compound, for example, the following dihydroxy compounds can be used: 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methylphenyl)propane 2,2-bis(4-hydroxy-3,5-diphenyl)propane, methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl )propane, 2,2-bis(4-hydroxy-(3-phenyl)phenyl)propane, 2 ,2-Bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-Bi Bis(4-hydroxy-3,5-dibromophenyl)propane, 1,1-bis(4-hydroxyphenyl)methane, 2,2-bis(4-hydroxyphenyl)ethane 2,2-bis(4-hydroxyphenyl)butane, 1,1 -Bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl) Diphenylmethane, 1,1-bis(4-hydroxyphenyl)-2-ethylhexane , 1,1-bis(4-hydroxyphenyl)decane, bis(4-hydroxy-3-nitro phenyl)methane, 3,3-bis(4-hydroxyphenyl)pentane, 1,3-bis( 2-(4-hydroxyphenyl)-2-propyl)benzene, 1,3-bis(2-(4- 2,2-bis(4-hydroxyphenyl)-2-propyl)benzene 1,1-bis(4-hydroxyphenyl)cyclohexane , bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenylsulfone bis(4-hydroxyphenyl)sulfide, bis(4-hydroxy-3-methylphenyl)sulfide phenyl)sulfide, bis(4-hydroxyphenyl)disulfide, 4,4'-dihydr 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether Aromatic bisphenol compounds such as 2,2-bis(4-(2-hydroxyethoxy) )phenyl)propane, 2,2-bis(4-(2-hydroxypropoxy)phenyl)propane propane, 1,3-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxy)benzene Bis(4-(2-hydroxyethoxy)phenyl)sulfonate Dihydroxy compounds having an ether group bonded to an aromatic group such as 9,9-bis(4- (2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-Bis(4-(2-hydroxypropoxy)phenyl)fluorene, 9,9-bis (4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis( 4-(2-hydroxypropoxy)-3-methylphenyl)fluorene, 9,9-bis( 4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bi Fluorene, 9,9- Bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-Bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluoro 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluoro 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)benzene Luoren, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6 -methylphenyl)fluorene, 9,9-bis(4-(3-hydroxy-2,2-dimethylphenyl)fluorene Dihydroxy compounds having a fluorene ring, such as (phenylpropoxy)phenyl)fluorene.
[0033] Examples of the diester compound include the following dicarboxylic acids: Taric acid, phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyl Phenyl ether dicarboxylic acid, 4,4'-benzophenone dicarboxylic acid, 4,4'-diphenyl Phenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, 2,6-naphthalene Aromatic dicarboxylic acids such as phthalenedicarboxylic acid; 1,2-cyclohexanedicarboxylic acid; Alicyclic compounds such as 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid Dicarboxylic acids; malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid Aliphatic dicarboxylic acids such as , azelaic acid, and sebacic acid. The dicarboxylic acid itself can be used as a raw material for polyester carbonate resin. Depending on the production method, dicarboxylic acid esters such as methyl esters and phenyl esters may be used. Alternatively, dicarboxylic acid derivatives such as dicarboxylic acid halides can be used as the raw material.
[0034] When other structural units are introduced into the polycarbonate resin of the present invention, the other structural units The content of is relatively small, and the heat resistance, refractive index, and compatibility with other resins are adjusted, and Improve the transparency of clear polycarbonate resin (compatibility of structural unit (1) and structural unit (2) Among the other structural units mentioned above, it is preferable to use the From the viewpoint of adjusting various physical properties such as mechanical properties, heat resistance, and refractive index without impairing the properties, Aromatic dihydroxy compounds, alicyclic dihydroxy compounds, and aromatic-containing dihydroxy compounds are preferred. Since the structural unit (2) has a structure with a relatively low refractive index, it is preferable to use an aromatic diamine having a high refractive index. By copolymerizing a hydroxy compound, the refractive index of the resulting polycarbonate resin can be increased. The polycarbonate resin of the present invention can be blended with other resins to adjust the direction of the viscosity. When used as a resin composition, the refractive index of the resulting resin should be matched to that of other resins. From the viewpoint of improving heat resistance and hardness, it is possible to improve the transparency of the resin composition. Aromatic and alicyclic dihydroxy compounds, acetal-containing dihydroxy compounds Among the above dihydroxy compounds, 1,4-cyclohexyl ester compounds and diester compounds are preferred. Xanthane dimethanol, tricyclodecane dimethanol, spiroglycol, 2,2-bis (4-hydroxyphenyl)propane is particularly useful.
[0035] When the polycarbonate resin of the present invention contains other structural units, The content of other structural units in the copolymer resin is preferably 1% by weight or more, and more preferably 2% by weight or more. More preferably, the content is 20% by weight or less, and more preferably, 10% by weight or less. Within the above range, the resin properties obtained from the structural units (1) and (2) are not impaired. without imparting other desired properties.
[0036] Copolymerization of aromatic dihydroxy compounds and diester compounds such as bisphenol compounds When used as a synthetic component, it may be possible to improve the heat resistance of polycarbonate resin. However, on the other hand, if polycarbonate resin contains a large amount of aromatic structures, its weather resistance decreases. In addition, bisphenol compounds and diester compounds, structural units (1) and structures Since there is a large difference in the polymerization reactivity of the dihydroxy compounds forming unit (2), Phenol compounds and diester compounds remain on the end groups, resulting in high molecular weight polycarbonates. It becomes difficult to obtain a carbonate resin, and mechanical properties such as impact resistance tend to decrease. If the reaction temperature is increased in an attempt to accelerate the reaction, the structural unit (1) will thermally decompose, resulting in Polycarbonate resins tend to become discolored. For these reasons, aromatic-containing dihydrocarbons The content of structural units derived from oxy compounds or diester compounds is preferably 15% by weight or less. It is preferably 10% by weight or less, more preferably 5% by weight or less.
[0037] [Method of producing the first polycarbonate resin] The first polycarbonate resin forms at least a structural unit represented by the formula (1). Dihydroxy compounds, dihydroxy compounds forming the structural unit represented by the formula (2), and It can be synthesized by polycondensation using a carbonic acid diester as the raw material through an ester exchange reaction. do. More specifically, the monohydroxy compound which is a by-product in the polycondensation and transesterification reaction is The reaction can be obtained by removing substances such as fluorine from the system.
[0038] In this step, a dihydroxy compound forming the structural unit (1) and a structural unit (2) are The dihydroxy compound to be formed is the same as that described above. In particular, the compound to form the structural unit (2) The dihydroxy compound is polytrimethylene ether glycol, The number average molecular weight of the ethylene ether glycol is preferably 200 or more and 2500 or less. The lower limit is more preferably 300 or more, even more preferably 400 or more, and particularly preferably 450 or more. The upper limit is preferably 2000 or less, more preferably 1500 or less, and more preferably 120 It is particularly preferably 0 or less, and most preferably 1100 or less. The transparency of the copolymer polycarbonate containing the structural unit (2) is improved. Polymer molecular chains containing unit (2) form soft segments, resulting in high tensile elongation. When the polycarbonate resin of the present invention is used as a modifier and blended with other resins, Furthermore, the impact resistance of the resin composition can be improved. is calculated from the hydroxyl value analysis described below.
[0039] The transesterification reaction is carried out using a transesterification catalyst (hereinafter, the transesterification catalyst is referred to as a "polymerization catalyst"). The type of polymerization catalyst determines the reaction rate of the ester exchange reaction, And it can have a significant effect on the quality of the resulting polycarbonate resin.
[0040] The polymerization catalyst is effective in improving the transparency, color tone, heat resistance, weather resistance, and other properties of the resulting polycarbonate resin. There is no particular limitation as long as it can satisfy the requirements for the above and mechanical properties. Group I or II in the long-form periodic table (hereinafter referred to simply as "Group 1" and "Group 2" (compounds of metals such as ammonium nitrate, ammonium nitrate, etc.) Basic compounds such as amine compounds and amine-based compounds can be used. Among them, Group 1 metal compounds are and / or Group 2 metal compounds are preferred.
[0041] Examples of Group 1 metal compounds include the following compounds: sodium hydroxide, water Potassium oxide, lithium hydroxide, cesium hydroxide, sodium bicarbonate, potassium bicarbonate Lithium hydrogen carbonate, cesium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate , cesium carbonate, sodium acetate, potassium acetate, lithium acetate, cesium acetate, stearyl acetate, Sodium stearate, potassium stearate, lithium stearate, cesium stearate ammonium, sodium borohydride, potassium borohydride, lithium borohydride, Cesium boron, sodium phenylborate, potassium phenylborate, phenylborate Lithium boron, cesium phenyl boron, sodium benzoate, potassium benzoate, Lithium benzoate, Cesium benzoate, Disodium hydrogen phosphate, Dipotassium hydrogen phosphate , dilithium hydrogen phosphate, dicesium hydrogen phosphate, disodium phenylphosphate, phenyl Dipotassium phenylphosphate, dilithium phenylphosphate, dicesium phenylphosphate, sodium Alcoholates, phenolates, and bisphenol A of potassium, lithium, and cesium Disodium salt, dipotassium salt, dilithium salt, dicesium salt, etc. Group 1 metal compounds In terms of polymerization activity and the color tone of the resulting polycarbonate resin, lithium compounds are preferred. I wish.
[0042] Examples of Group 2 metal compounds include the following compounds: calcium hydroxide, water Barium oxide, magnesium hydroxide, strontium hydroxide, calcium bicarbonate, carbonate Barium hydrogen carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium carbonate, carbonic acid Barium, magnesium carbonate, strontium carbonate, calcium acetate, barium acetate, vinegar Magnesium acetate, Strontium acetate, Calcium stearate, Barium stearate , magnesium stearate and strontium stearate. Group 2 metal compounds The catalyst is preferably a magnesium compound, a calcium compound or a barium compound, and has a polymerization activity and From the viewpoint of the color tone of the obtained polycarbonate resin, a magnesium compound and / or a calcium compound More preferred are ammonium compounds, and most preferred are calcium compounds.
[0043] In addition, a basic boronization reaction may be carried out in conjunction with the Group 1 metal compound and / or the Group 2 metal compound. basic compounds such as basic phosphorus compounds, basic ammonium compounds, and amine compounds However, it is preferable to use only Group 1 metal compounds and / or Group 2 metal compounds. From the viewpoint of the color tone of the resulting polycarbonate resin, it is more preferable to use a Group 2 metal It is most preferred that the compound be used alone.
[0044] The amount of the polymerization catalyst used was 1 μm per 1 mol of the total dihydroxy compound used in the reaction. ol or more is preferable, 3 μmol or more is more preferable, and 5 μmol or more is particularly preferable. The amount of polymerization catalyst used was 30 moles per mole of the total dihydroxy compounds used in the reaction. 0 μmol or less is preferable, 200 μmol or less is more preferable, and 100 μmol or less is more preferable. is particularly preferred.
[0045] By adjusting the amount of the polymerization catalyst used within the above range, the polymerization rate can be increased. Therefore, it is possible to obtain a polycarbonate resin having a desired molecular weight without necessarily increasing the polymerization temperature. Therefore, deterioration of the color tone of the polycarbonate resin can be suppressed. In addition, the unreacted raw materials volatilize during the polymerization, and the molar ratio of the dihydroxy compound and the carbonate diester decreases. This prevents the copolymerization ratio from being degraded, allowing the production of resins with the desired molecular weight and copolymerization ratio. Furthermore, the occurrence of side reactions can be suppressed, so that the poly This makes it possible to further prevent the carbonate resin from becoming discolored during molding.
[0046] Among the group 1 metals, sodium, potassium, and cesium have the greatest influence on the color tone of polycarbonate resin. Considering the adverse effects of iron on the color tone of polycarbonate resin, The total content of sodium, potassium, cesium, and iron in carbonate resin is 1 pp by weight. In this case, the deterioration of the color tone of the polycarbonate resin is more suppressed. This can further prevent the color change and improve the color tone of the polycarbonate resin. From a similar perspective, sodium, potassium, and cesium in polycarbonate resin can be The total content of , and iron is more preferably 0.5 ppm by weight or less. These metals can come not only from the catalysts used, but also from the raw materials and reactors. Regardless, the total amount of compounds of these metals in the polycarbonate resin is sodium It is preferable that the total content of potassium, cesium and iron is within the above-mentioned range.
[0047] The method for polycondensing a dihydroxy compound and a carbonic acid diester is to carry out the polycondensation of the dihydroxy compound and the carbonic acid diester in the presence of the above-mentioned catalyst. The reaction is carried out in multiple stages using multiple reactors. The reaction can be carried out in batch, continuous, or batch mode. There is a method that combines the batch type and the continuous type, but it is a method that can produce polycarbonate resin with less heat history. It is preferable to adopt a continuous type which is excellent in productivity and can obtain a desired amount.
[0048] From the viewpoint of controlling the polymerization rate and the quality of the resulting polycarbonate resin, It is important to appropriately select the jacket temperature, internal temperature, and pressure in the reaction system. In the early stage of the polycondensation reaction, a prepolymer is obtained at a relatively low temperature and low vacuum, and after the reaction In the latter stage, it is preferable to increase the molecular weight to a predetermined value at a relatively high temperature and high vacuum. In this case, the distillation of unreacted monomers is suppressed, and the dihydroxy compound and the carbonate diester are reacted. As a result, the decrease in the polymerization rate can be suppressed. It is also possible to more reliably obtain polymers with the desired molecular weight and terminal groups. do.
[0049] By adjusting the temperature of the polycondensation reaction, productivity can be improved and the heat history of the product can be prevented from increasing. In addition, it is possible to prevent the volatilization of monomers and the decomposition and coloring of polycarbonate resin. Specifically, the reaction conditions for the first stage reaction are as follows: The following conditions can be adopted: The maximum temperature inside the polymerization reactor is usually 16 In the range of 0 to 230°C, preferably 170 to 220°C, and more preferably 180 to 210°C. The pressure of the polymerization reactor (hereinafter, pressure refers to absolute pressure) is usually set to 1 to 11 The pressure is set to 0 kPa, preferably 5 to 50 kPa, and more preferably 7 to 30 kPa. The reaction time is usually set within the range of 0.1 to 10 hours, preferably 1 to 5 hours. The first stage reaction is carried out while distilling off the generated monohydroxy compound from the reaction system. It is preferable that
[0050] From the second stage onwards, the pressure in the reaction system is gradually lowered from the first stage pressure to While removing the hydroxy compounds from the reaction system, the pressure (absolute pressure) of the reaction system is finally increased to 1 The maximum internal temperature of the polymerization reactor is usually 200 to 400 kPa. 260°C, preferably 210 to 240°C, and particularly preferably 215 to 230°C. The reaction time is usually 0.1 to 10 hours, preferably 0.5 to 5 hours, and particularly preferably Or set it in the range of 1 to 3 hours.
[0051] Once it has been confirmed that the specified melt viscosity (molecular weight) has been reached using the stirring power as an indicator, Inject nitrogen into the reactor to return the pressure to normal pressure, or remove the molten resin from the reactor. The polymerization reaction is stopped by extruding the molten resin from the die head in the form of strands. The mixture is cooled and solidified, and then pelletized using a rotary cutter or similar. If necessary, the mixture is pelletized. The process of extrusion devolatilization, extrusion kneading, and extrusion filtration may be added to the above. Combine the two, evaporate low molecular weight components using a vacuum vent, or use a polymer filter to remove foreign matter. In the examples described later, some resins do not solidify at room temperature. In such cases, The molten resin after the reaction is extracted in a lump state, and when it is used for molding or evaluation, the resin is cut into pellets. I took it out and used it.
[0052] [Additives] In the range not impairing the effects of the present invention, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, Fillers and other filling agents, neutralizing agents, lubricants, anti-fog agents, anti-blocking agents, slip agents, Powders, colorants, flame retardants, antistatic agents, conductive agents, crosslinking agents, crosslinking assistant agents, metal deactivators , molecular weight regulators, antibacterial agents, antifungal materials, fluorescent brighteners, organic and inorganic light diffusing agents, etc. These additives can be used within the range that does not impair the effects of the present invention.
[0053] When the first polycarbonate resin is used as a modifier and blended with other resins, the first polycarbonate resin is melt extruded. Since the mixture is kneaded, the polymerization catalyst is deactivated in order to improve stability during melt processing. It is preferable to add an acidic compound for (neutralizing) the acid and an antioxidant. Of these, phosphonic acid and phosphonic acid esters are particularly preferred. The acidic compound is a polymerization catalyst metal in the resin. It is preferable to add an amount of 0.5 to 3 times the molar amount of the compound.
[0054] [Characteristics of the first polycarbonate resin] Biomass ratio In the present invention, the biomass content of the first polycarbonate resin is The weight ratio of structural units synthesized from plant-derived resources among all structural units constituting the resin The first polycarbonate resin preferably has a biomass content of 80% by weight or more. It is preferable that the content is 85% by weight or more. In the examples described later, ISB, PO3G, 1,3-PDO is synthesized from plant-derived resources, and other PEG, PP G, PTMG, CHDM, and DPC are synthesized from fossil resources. The biomass content of polycarbonate resin synthesized using these is determined by the structural unit derived from ISB. , the weight ratio of structural units derived from PO3G, and structural units derived from 1,3-PDO It is the sum of the rates.
[0055] ·Transparency The first polycarbonate resin may be transparent or opaque, which allows for a wider range of applications. From the viewpoint of transparency, it is preferable that the polycarbonate of the present invention is transparent. Resin hardens at temperatures below room temperature, making it difficult to mold into a specific shape. The resin pellets obtained are visually evaluated as to whether they are transparent or opaque.
[0056] ·Hue The hue of the first polycarbonate resin can be evaluated by the YI of the pellets described later. The absolute value of YI of the pellet is preferably 30 or less, more preferably 20 or less, and more preferably 15 or less. The bottom is especially preferred.
[0057] -Flexibility (tensile elongation, tensile modulus) The flexibility of the first polycarbonate resin is evaluated by the tensile elongation and tensile modulus described later. The tensile elongation of the first polycarbonate resin is preferably 300% or more. More preferably, the ratio is 400% or more, and particularly preferably 450% or more. The tensile modulus is preferably 100 MPa or less, more preferably 70 MPa or less, and more preferably 50 MPa or less. When the above range is satisfied, it is possible to use the resin in applications requiring toughness or in applications requiring resistance to other resins. It can be suitably used as an impact improver.
[0058] ·Thermal stability The thermal stability of the first polycarbonate resin can be evaluated by the 5% weight loss temperature described later. The 5% weight loss temperature of the first polycarbonate resin is preferably 330°C or higher. ℃ or more is more preferable, and 350 ℃ or more is particularly preferable. This makes it possible to sufficiently suppress the deterioration of the properties due to the thermal decomposition of the material.
[0059] ·Number average molecular weight The number average molecular weight of the first polycarbonate resin is preferably 15,000 or more and 50,000 or less. The lower limit is preferably 20,000 or more, more preferably 25,000 or more, and more preferably 300 The upper limit is preferably 48,000 or less, and more preferably 45,000 or less. Within the above range, high tensile elongation, excellent flexibility and impact resistance can be obtained, and other When mixed with resin, it easily forms a phase separation morphology suitable for impact resistance. In addition, This reduces stickiness and prevents pellets from fusing together when used in pellet form. The number average molecular weight of the first polycarbonate resin is as described below. 1 Calculated by H-NMR analysis It is served.
[0060] [Applications of the first polycarbonate resin] The polycarbonate resin of the present invention is excellent in transparency, thermal stability, flexibility, etc., and therefore has a high resistance to water. Vibration materials, vibration-damping materials, cushioning materials, soundproofing materials, sound-absorbing materials, footwear applications, sealing materials, various grips, medical use Viscosity modifiers added to adhesives, oils and lubricants, agricultural films, 3D It can be used as a printer modeling material, a resin modifier, etc. Among other things, it has excellent impact resistance and flexibility. It is preferable to use it by kneading with other resins as a modifier for improving the properties.
[0061] [Polycarbonate resin composition] The second aspect of the present invention is a method for producing a polycarbonate resin having a structure represented by the formula (1) A polycarbonate resin having a structure different from that of the first polycarbonate resin. A resin composition containing a second polycarbonate resin (hereinafter, sometimes referred to as a second polycarbonate resin) The second polycarbonate resin contains 40% by weight or more of the structural unit represented by the formula (1). The first polycarbonate resin and the second polycarbonate resin are each contained in an amount of 90% by weight or less. The polycarbonate resin composition has a content ratio of 1 / 99 to 99 / 1. In the polycarbonate resin composition of the present invention, the first polycarbonate resin and the second polycarbonate resin The weight ratio of the carbonate resin is preferably 2 / 98 to 90 / 10, more preferably 3 / 97 to 80 / It is more preferable that the ratio is 20, and particularly preferably 5 / 95 to 70 / 30. It is possible to achieve a high level of balance between various physical properties such as heat resistance, impact resistance, and transparency. The first polycarbonate resin and the second polycarbonate resin each contain the structural unit (1). However, the resin structures are different from each other. Specifically, for example, the structures constituting each resin are The content of unit (1), copolymerization components, molecular weight, etc. are different.
[0062] [Second polycarbonate] The content of the structural unit (1) in the second polycarbonate resin is 40% by weight or more and 90% by weight or less. The lower limit is preferably 45% by weight or more, and more preferably 50% by weight or more. The upper limit is preferably 80% by weight or less, more preferably 75% by weight or less. is particularly preferred.
[0063] The second polycarbonate resin is an aliphatic dihydroxy compound or an alicyclic dihydroxy compound. or other structural units, and the content of these units is 1 wt. % or more and 70% or less by weight. The lower limit is preferably 5% or more by weight, and more preferably 10% or less by weight. The upper limit is more preferably 60% by weight or less, and further preferably 50% by weight or less. It is particularly preferable that the content is 40% by weight or less.
[0064] In particular, aliphatic dihydroxy compounds and alicyclic dihydroxy compounds have a flexible molecular skeleton. Therefore, when the content of structural units derived from these is within the above range, the polymer has a durability suitable for melt processing. In addition to improving thermal resistance and fluidity, mechanical properties such as tensile elongation and impact resistance are also improved. It is preferable because it is possible to obtain aliphatic dihydroxy compounds and alicyclic dihydroxy compounds. The dihydroxy compound used in the first polycarbonate resin is the same as that in the first polycarbonate resin. However, because of its excellent balance of heat resistance and mechanical properties, 1,4-cyclohexanediaminetetraacetate is preferred. It is particularly preferred to use methanol and tricyclodecane dimethanol.
[0065] The second polycarbonate resin is a mixture of an aliphatic dihydroxy compound and an alicyclic dihydroxy compound. The structural unit may contain structural units other than the structural units derived from the above. As in the first embodiment, the compounds include ether-containing dihydroxy compounds, acetal-containing Dihydroxy compounds having an aromatic structure, dihydroxy compounds having an aromatic structure, and diester compounds Some examples include:
[0066] The second polycarbonate resin may contain a structural unit represented by the structural unit (2). The content is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably It is more preferably 5% by weight or less. 2 The polycarbonate resin undergoes moderate phase separation, enabling it to exhibit high impact resistance.
[0067] [Characteristics of the second polycarbonate resin] Biomass ratio The biomass content of the second polycarbonate resin is preferably 40% by weight or more. It is more preferably 50% by weight or more, and particularly preferably 55% by weight or more.
[0068] Glass transition temperature The second polycarbonate resin preferably has a glass transition temperature of 90°C or higher and 200°C or lower. The lower limit is more preferably 100° C. or higher, even more preferably 110° C. or higher, and particularly preferably 120° C. or higher. The upper limit is preferably 180° C. or less, more preferably 160° C. or less, and more preferably 15 Within this range, the composition can be used in a wide range of applications, and the melt processing temperature is preferably 0° C. or lower. It is easy to process and has good mechanical properties such as tensile elongation and impact resistance. The glass transition temperature of the second polycarbonate resin is measured by a differential scanning calorimeter described below. The glass transition temperature of the resin can be changed by changing the type of structural unit constituting the resin, the copolymerization ratio, etc. You can adjust it appropriately by changing the
[0069] ·Number average molecular weight The number average molecular weight of the second polycarbonate resin is preferably 8,000 or more and 30,000 or less. The lower limit is more preferably 8500 or more, and particularly preferably 9000 or more. The upper limit is 2500 It is more preferable that the molecular weight is 0 or less, and particularly preferable that the molecular weight is 20,000 or less. It has an excellent balance of mechanical properties and fluidity during melt molding. Number of second polycarbonate resins The average molecular weight is described below. 1 Calculated by H-NMR analysis.
[0070] [Method of producing second polycarbonate resin] The second polycarbonate resin is a di-olefin having at least the structural unit represented by (1) above. By transesterification using monomer raw materials containing hydroxy compounds and carbonate diesters, It can be synthesized by a polycondensation process. The monomer raw material may be, for example, an aliphatic dihydroxy compound or an alicyclic dihydroxy compound. As the aliphatic dihydroxy compound or the alicyclic dihydroxy compound, The dihydroxy compound preferably used is the same as that in the first polycarbonate resin, Among these, 1,4-cyclohexafluoroethylene is the most popular due to its excellent balance of heat resistance and mechanical properties. It is particularly preferred to use tricyclodecane dimethanol and tricyclodecane dimethanol.
[0071] [Additives for the polycarbonate resin composition of the present invention] The polycarbonate resin composition of the present invention comprises a first polycarbonate resin, a second polycarbonate resin, In addition to the ester resin, other components such as additives may be included. For example, polycarbonate, aromatic polyester, aliphatic polyester, etc., to the extent that it does not impair the , polyamide, polystyrene, polyolefin, amorphous polyolefin, acrylic Resin, acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile Synthetic resins such as styrene-styrene copolymers (AS resins); acrylic rubber, butadiene rubber, etc. Elastomers; biodegradable resins such as polylactic acid and polybutylene succinate; Alternatively, two or more of the above-mentioned polycarbonate resins may be kneaded together. The carbonate resin composition may be a polymer alloy.
[0072] As other components, a relatively small amount of a compound compatible with the first polycarbonate resin is used. By doing so, the properties of the polycarbonate resin composition can be further improved. As a compound compatible with carbonate resin, 50% by weight of a structural unit represented by the following formula (3) is used: The structural unit represented by the formula (3) is preferably an acrylic resin having a structural unit content of at least 1. These units are sometimes referred to as “construction units (3).”
[0073] [ka] In formula (3), R 1 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms which may have a substituent. R 2 is an optionally substituted aryl group, an optionally substituted aralkyl group It is a kill group.
[0074] In one embodiment, the present inventors have found that the acrylic resin is a first polycarbonate resin. It was found that the first polycarbonate resin is compatible with the second polycarbonate resin and is incompatible with the first polycarbonate resin. To produce it, in the formula (3), R 1 is preferably a hydrogen atom or a methyl group, R 2 is preferably a phenyl group or a benzyl group. The vinyl compounds formed include phenyl acrylate, phenyl methacrylate, phenyl acrylate, Among them, phenyl acrylate, benzyl methacrylate, etc. are preferred. Phenyl methacrylate is preferred, and particularly phenyl acrylate.
[0075] The acrylic resin is a homopolymer that does not substantially contain any structural unit other than the structural unit (3). or a copolymer acrylic resin containing a structural unit other than the structural unit (3). From the viewpoint of compatibility between the acrylic resin of the present invention and the first polycarbonate resin, The content of the structural unit (3) in the vinyl resin is preferably 50% by weight or more, more preferably 70% by weight or more. It is more preferable, and particularly preferable that the content is 90% by weight or more.
[0076] Examples of vinyl compounds forming structural units other than the structural unit (3) include methyl acrylate. , ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, methyl ethyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, acrylonitrile, styrene, α-methylstyrene, butadiene, etc. Among them, from the viewpoint of improving thermal stability and mechanical properties, methyl acrylate can be used. The structural units other than the structural unit (3) are preferably the first polymer. Since it is not compatible with carbonate resins, it is preferable to keep the content relatively small. The content in the acrylic resin is preferably 10% by weight or less, and particularly preferably 5% by weight or less. It is.
[0077] In the resin composition of the present invention, the acrylic resin comprises a first polycarbonate resin. The first polycarbonate resin and the second polycarbonate resin are mixed in the same phase and adjust the refractive index. Carbonate resins are not completely compatible, so phase separation occurs when they are mixed. Since the refractive index of the first polycarbonate resin and the second polycarbonate resin are usually different, the resin composition is completely The refractive index of the first polycarbonate resin is usually less than that of the second polycarbonate resin. Since the refractive index of the first and second polycarbonate resins is lower than that of the first polycarbonate resin, the refractive index of the second polycarbonate resin is higher than that of the first and second polycarbonate resins. By mixing the acrylic resin, which has a refractive index of 100%, in an appropriate ratio, the refractive index of the two phases can be matched. This makes it possible to improve the transparency of the resin composition. In order not to impair the inherent properties of the acrylate resin, the amount of acrylic resin added is comparatively small. In order to obtain the effect of increasing the refractive index even with a small amount, it is preferable to use an acrylic The refractive index of the resin is preferably 1.54 or more and 1.65 or less. The lower limit is 1.55 or more. More preferably, the upper limit is 1.63 or less, and particularly preferably 1.56 or more. When the refractive index is within the above range, the amount of the acrylic resin added is preferably 1.60 or less. can be kept to a small amount.
[0078] The polycarbonate resin composition of the present invention contains polytrimethylene ether glycol. As you can imagine, PO3G is highly compatible with the first polycarbonate resin. Since the structural unit (2) in the first polycarbonate resin dissolves in the phase, the soft segment The impact resistance can be further improved by lowering the glass transition temperature of the olefin resin.
[0079] The number average molecular weight of PO3G is preferably 300 or more and 10,000 or less. The lower limit is 500 or more. More preferably, the number is 1000 or more, and particularly preferably 2000 or more. It is more preferably 8000 or less, and particularly preferably 5000 or less. It is compatible with polycarbonate resin and does not easily break down during melt processing or after molding. This can suppress login.
[0080] Other components include elastomers such as acrylic rubber and butadiene rubber. Among these, from the viewpoint of excellent impact resistance and transparency of the resin composition, A is preferable. It is preferable that the rubber contains an acrylic rubber, and in particular, that the rubber contains an acrylic rubber having a core-shell structure. Of these, alkyl acrylate / alkyl methacrylate / styrene It is particularly preferred that the polymer is a copolymer.
[0081] [Method of producing resin composition] The resin composition can be prepared, for example, by mechanically melt-kneading the above-mentioned components constituting the resin composition. The melt kneader can be, for example, a single screw extruder or a twin screw extruder. , Brabender, Banbury mixer, kneader blender, roll mill, etc. When mixing, each component can be mixed at once, or after mixing any component. Alternatively, a multi-stage division kneading method may be used in which the remaining components are added and kneaded. Using a twin-screw extruder equipped with a casing, each component is continuously charged to continuously obtain a resin composition. The lower limit of the kneading temperature is usually 150° C. or more, and the lower limit of the kneading temperature is preferably 150° C. or more. The kneading temperature is preferably 180° C. or higher, and more preferably 200° C. or higher. 80°C or less, preferably 260°C or less, more preferably 250°C or less, and particularly preferably 2 The temperature is 40°C or lower. When the temperature is within this range, thermal deterioration caused by heating in the kneader or heat generation due to shearing is suppressed. At the same time, productivity (mixing processing speed) is increased.
[0082] [Characteristics of polycarbonate resin composition] Biomass ratio The resin composition of the present invention preferably has a biomass content of 50% by weight or more. % by weight or more is more preferable, 60% by weight or more is even more preferable, and 65% by weight or more is particularly preferable. In order to obtain a high biomass content, it is necessary to use structural units (1) made from plant-derived raw materials. and structural unit (2) as much as possible while optimizing the blending so as to obtain the desired physical properties. It needs to be optimized.
[0083] Impact strength The resin composition of the present invention has an Izod impact value of 15 kJ / m 2 It is preferable that the resistance is 20 kJ / m or more. 2 More preferably, 30 kJ / m or more. 2 The above It is particularly preferable that the above range is satisfied, since the impact strength is sufficiently high and the impact resistance is high. It is used in applications such as automobile interior parts where durability is required, and fittings where damage is likely to occur due to stress concentration. The present invention can also be applied to molded articles having various shapes and sizes.
[0084] ·Heat resistance The resin composition of the present invention has a deflection temperature under load of 90° C. or more, as measured by the method described below. The lower limit is preferably 50° C. or lower, more preferably 92° C. or higher, particularly preferably 95° C. or higher. The upper limit is more preferably 140° C. or less, and particularly preferably 135° C. or less. It has practical heat resistance, as well as mechanical properties such as impact resistance and melt processability. Excellent.
[0085] ·Transparency When the resin composition of the present invention is applied to an application requiring transparency, the transparency is measured by the method described below. It is preferable that the haze value is set to 40% or less. In this case, 20% or less is preferable. More preferably, it is 10% or less, even more preferably, it is 5% or less, and most preferably, it is 1% or less. When the colorant is in the above range, it is possible to obtain a coloring material that develops a sharp color by blending the colorant with the resin. This can be applied to components that require transparency.
[0086] [Method of manufacturing molded products] The polycarbonate resin and polycarbonate resin composition of the present invention can be molded, for example, by injection molding. Insert molding, two-color molding, sandwich molding, gas injection molding, etc.) Extrusion molding, inflation molding, T-die film molding, lamination molding, blow -Molding, blow molding, compression molding, calendar molding, and other molding methods are used to create various molded products. There are no particular limitations on the shape of the molded product, and it can be in the form of a sheet, film, plate, granule, etc. Examples of the material include particles, lumps, fibers, rods, porous bodies, and foams. Preferably, the material is a sheet or film. The formed film can be uniaxially or biaxially stretched. Examples of the stretching method include a roll method, a tenter method, and a tubular method. Surface treatments such as corona discharge treatment, flame treatment, plasma treatment, ozone treatment, etc., commonly used in industry It is also possible to apply reason.
[0087] [Application] The uses of the molded products are not particularly limited, but the polycarbonate resin and polycarbonate of the present invention are The resin composition has excellent mechanical properties as well as weather resistance and optical properties, making it suitable for use in automotive interiors. Components and exterior materials, building materials used outdoors (lighting covers, carports, highway soundproofing walls, etc.) ), the front panel of a display, the housing of an electric / electronic device, etc. EXAMPLES
[0088] The present invention will be described in more detail below using examples. The following examples are not intended to be limiting unless otherwise stated.
[0089] [Measurement method] Various physical properties were measured according to the following methods.
[0090] · Number average molecular weight of polytrimethylene ether glycol (PO3G) Polytrimethylene was synthesized using an acetylation reagent in accordance with JIS K1557-1. The hydroxyl value of the ether glycol was measured. The number average molecular weight was calculated from the hydroxyl value using the following formula: The same procedure was carried out for PEG, PPG, and PTMG, which will be described in the Examples below. The number average molecular weight was measured. Number average molecular weight = 1 / (hydroxyl value / 1000 / 56.11 / 2) Unit of hydroxyl value: mg-KOH / g-polymer 56.11: Molecular weight of calcium hydroxide (KOH)
[0091] Number average molecular weight of polycarbonate resin Approximately 15 mg of polycarbonate resin sample was weighed out and dissolved in approximately 0.7 mL of deuterated chloroform. This was placed in an NMR tube with an inner diameter of 5 mm.1 H-NMR spectrum was measured. The signal based on the structural units derived from each dihydroxy compound that constitutes the recarbonate resin The number average molecular weight was calculated from the intensity ratio of the signal of each terminal group and the signal of each terminal group. It is as follows: Equipment: JNM-ECZ400S (manufactured by JEOL Ltd.) ·Measurement temperature: 30℃ Relaxation time: 6 seconds Number of times accumulated: 64
[0092] For example, the copolymer polycarbonate of ISB and PO3G500 1 The H-NMR analysis is as follows: Do as follows: [Range for calculating integral value] (a): 5.4-4.4 ppm: all ISB repeating unit derived (proton count: 4, molecular Amount:172.14) (b): 2.2-1.5 ppm: All PO3G500 repeating structural units (proton count: 17.63, molecular weight: 539.99) (c): 4.4 ppm: from ISB hydroxyl end group (proton number: 1) (d): 2.6 ppm: from ISB hydroxyl end group (proton number: 1) (e): 7.4 ppm: derived from DPC end groups (proton number: 2, molecular weight: 93.10) In addition, double bond ends may be generated from ISB and PO3G by thermal decomposition. However, in the examples described below, the amount was so small that it could be ignored. The amount of the terminal group was also below the lower limit of quantification. [Calculation of the value equivalent to the number of moles of each structure] Total ISB repeating units (a´): (a) integral value / 4 Total PO3G500 repeating structural units (b´): (b) integral value / 17.63 ISB hydroxyl end group (c´): (c) integral value + (d) integral value DPC end group (e´): (e) integral value / 2 [Calculation of number average molecular weight] (a´×172.14+b´×539.99+e´×93.10) / {(c´+e´) / 2}
[0093] Pellet color The color of polycarbonate resin pellets is measured by spectrophotometric colorimetry in accordance with ASTM D1925. The measurement was performed using a CM-5 (Konica Minolta) with reflected light. The measurement conditions were a measurement diameter of 3 0 mm, SCE was selected. The calibration glass for petri dish measurement, CM-A212, was fitted into the measurement section. Then, place the CM-A124 zero calibration box over it to perform zero calibration. A cylindrical glass container with an inner diameter of 30 mm and a height of 50 mm was used for white calibration. The pellets were packed to a depth of about 40 mm and the YI value was measured. It indicates that the color has little yellowish or other coloring and has excellent hue.
[0094] TG-DTA As an index of the thermal stability of polycarbonate resin, thermogravimetric differential thermal analysis (TG-DTA) The 5% weight loss temperature was measured using a thermogravimetric differential calorimeter TG-DTA 2000SA (NE Using a 10 mg sample (manufactured by TZSCH Japan), place approximately 10 mg of sample in an aluminum pan. In a nitrogen atmosphere with a nitrogen flow rate of 100 mL / min, the temperature was increased from 30°C to 5°C at a rate of 10°C / min. The temperature was raised to 100°C. The weight of the sample was reduced by 5% from the weight when the sample temperature was 100°C. The temperature at which the weight loss rate is 5% was determined as the 5% weight loss temperature. The higher the 5% weight loss temperature, the better the thermal stability. Represents.
[0095] Tensile Test Approximately 5g of resin pellets are placed on a SUS spacer measuring 14cm in length, 14cm in width, and 0.1mm in thickness. The sample was heated at a temperature of 150 to 170°C with Teflon sheets placed on top and bottom of the sample. Preheat for 3 minutes, pressurize at 7MPa for 5 minutes, remove with spacer, cool and fill. A rectangular sample with a width of 10 mm and a length of 100 mm was cut from the obtained film. Then, a bench-top precision universal testing machine, AUTOGRAPH AGS-X (manufactured by Shimadzu Corporation), By using The tensile test was performed with an initial chuck distance of 50 mm and a tensile speed of 50 mm / min. The tensile elongation (breaking elongation) and tensile modulus were measured. The higher the tensile elongation and the lower the tensile modulus, It represents excellent flexibility.
[0096] Glass transition temperature The glass transition temperature was measured using a differential scanning calorimeter DSC6220 (SII Nano Technology Co., Ltd.). Approximately 10 mg of resin was placed in an aluminum pan manufactured by the same company, sealed, and then measured using a 50 ml Measurement was started at 200°C under a nitrogen gas flow of 100 L / min, and the temperature was cooled to 30°C at a rate of 20°C / min. The temperature was kept at 30°C for 3 minutes, and then the temperature was increased again to 200°C at a rate of 20°C / min. From the C data, a straight line extending the low-temperature baseline to the high-temperature side and a step-like change in the glass transition The extrapolated glass temperature is the temperature at the intersection of the tangent drawn at the point where the gradient of the curve of the extrapolated part is maximum. The onset temperature of the glass transition was determined and taken as the glass transition temperature.
[0097] Refractive Index A rectangular test piece 40 mm long and 8 mm wide was cut from the film produced by the above-mentioned heat pressing method. The specimen was cut out and used as the measurement sample. The refractive index nD was measured using a Tago multi-wavelength Abbe refractometer DR-M4 / 1550. Monobromonaphthalene was used as the interface liquid, and the reaction was carried out at 20°C.
[0098] Izod impact strength According to ASTM D256, a 3.2 mm thick notched test piece was used at 23°C. Izod impact strength (unit: kJ / m 2 The test pieces were prepared as follows: The resin pellets were vacuum dried at 90°C for more than 5 hours, and then molded in a small injection molding machine C. Izod test specimens were prepared using Mobile-0813 (manufactured by Shinko Selvick Co., Ltd.). The test piece was cut using a cutter and a notch with a tip radius of 0.25 mm was made. The higher the impact strength value, the better the impact resistance.
[0099] Heat deflection temperature (HDT) The resin pellets were vacuum dried at 90°C for more than 5 hours, and then injected into an injection molding machine EC-75 (Toshiba Machinery Co., Ltd.) An ISO test piece for mechanical properties was obtained using a 100 mm diameter steel sheet (manufactured by Kikaisha). A rectangular test piece measuring 0 mm in length, 10 mm in width, and 4 mm in thickness was then cut out. (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K7191-1, flatwise method, bending The deflection temperature under load of the rectangular test piece was determined at a stress of 1.8 MPa. The deflection temperature under load is high. The higher the value, the more excellent the heat resistance.
[0100] Haze Using the injection molding machine EC-75 mentioned above, a preform with a width of 60 mm, length of 60 mm, and thickness of 3 mm was The haze meter NDH2000 (Nihon Denki) was used in accordance with JIS K7136. The haze of the plate molded product was measured using a colorimeter (manufactured by Iki Kogyo Co., Ltd.) under a D65 light source. The lower the value, the more excellent the transparency.
[0101] (Raw materials used) The abbreviations and manufacturers of the compounds used in the following Examples and Production Examples are as follows.
[0102] [Dihydroxy compounds] ISB: Isosorbide (manufactured by Rocket Fleuret) PO3G500: Polytrimethylene ether glycol, measured number average molecular weight 514 ( Manufactured by ALLESSA, product name: VELVETOL) PO3G650: Polytrimethylene ether glycol, measured number average molecular weight 715 ( (Manufactured by ALLESSA) PO3G1000: Polytrimethylene ether glycol, number average molecular weight measured: 104 3 (ALLESSA) PO3G2700: Polytrimethylene ether glycol, number average molecular weight measured: 262 8 (ALLESSA) PEG600: Polyethylene glycol, number average molecular weight measured at 581 (Sanyo Chemical Industries, Ltd.) (Manufacturer) PPG600: Polypropylene glycol, number average molecular weight measured at 597 (Sanyo Chemical Industries Company) PTMG650: Polytetramethylene glycol, number average molecular weight 653 (Mitsubishi Keihin) (Mical Corporation) CHDM: 1,4-cyclohexanedimethanol (SK Chemical) 1,3-PDO: 1,3-propanediol (manufactured by DuPont) BPA: 2,2-bis(4-hydroxyphenyl)propane (Mitsubishi Chemical Corporation)
[0103] [Carbonate diester] DPC: Diphenyl carbonate (Mitsubishi Chemical) [Catalyst deactivator] Phosphonic acid (Tokyo Chemical Industry Co., Ltd.) [Heat stabilizer (antioxidant)] Irganox 1010: Pentaerythritol-tetrakis(3-(3,5-di-t ert-butyl-4-hydroxyphenyl)propionate (BASF) AS2112: Tris(2,4-di-tert-butylphenyl)phosphite (AD (Manufactured by EKA)
[0104] [Acrylic resin] PPhMA: Phenyl methacrylate / methyl acrylate = 99 / 1 weight% copolymer It was synthesized according to the method described in JP 2010-116501 A. [Impact modifier] Acrylic core-shell rubber: butyl acrylate-methyl methacrylate-styrene copolymer (Core: butyl acrylate, shell: methyl methacrylate, styrene)
[0105] (Example 1-1) PC1-1 Polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with stirring blades and reflux condensers. The mixture was 46.69 parts by weight (0.320 mol) of ISB and 42. 83 parts by weight (0.083 mol), 86.30 parts by weight (0.403 mol), and and calcium acetate monohydrate 2.13×10 -3 Part by weight (1.21×10 -5 m The inside of the reactor was replaced with nitrogen under reduced pressure, and then heated with a heat medium until the inside temperature reached Stirring was started when the temperature reached 100°C. After 40 minutes from the start of the temperature increase, the internal temperature reached 210°C. The temperature was controlled to be maintained at this temperature, and pressure reduction was started at the same time. After the temperature reached 210°C, The pressure was reduced to 13.3 kPa in 0 minutes. The phenol vapor by-produced during the polymerization reaction was reduced to 110°C. The small amount of monomer components contained in the phenol vapor is returned to the reactor and condensed. The unreacted phenol vapor was collected by condensing it at 45°C. Nitrogen was introduced into the first reactor. Once the pressure is restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor is transferred to the second reactor. Then, the temperature and pressure in the second reactor were increased, and the internal temperature reached 220°C and the pressure reached 100°C in 40 minutes. The pressure was then further reduced and polymerization was continued until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore the pressure, and the produced polystyrene was The carbonate was extruded into water and the strands were cut to obtain pellets. The resulting copolymer is called "PC1-1". The ratio of structural units derived from each monomer is ISB / PO3 G500 / DPC=46.1 / 42.7 / 11.3% by weight. The results are shown in Table 1. The resin obtained was transparent, had a good color, and exhibited high tensile elongation.
[0106] (Example 1-2) PC1-2 The raw materials were ISB 29.71 parts by weight (0.203 mol), PO3G500 6 1.87 parts by weight (0.120mol), DPC 69.34 parts by weight (0.324mol) , calcium acetate monohydrate 2.28 x 10 -3 Part by weight (1.29×10 -5 mol) Other than that, the same procedure as in Example 1-1 was carried out.
[0107] (Example 1-3) PC1-3 The raw materials were ISB 46.69 parts by weight (0.320 mol), PO3G650 4 3.42 parts by weight (0.061 mol), DPC 81.45 parts by weight (0.380 mol) , calcium acetate monohydrate 2.01 x 10 -3 Part by weight (1.14×10 -5 mol) Other than that, the same procedure as in Example 1-1 was carried out.
[0108] (Example 1-4) PC1-4 The raw materials were ISB 25.47 parts by weight (0.174 mol), PO3G 1000 68.30 parts by weight (0.065 mol), DPC 51.36 parts by weight (0.240 mol) ), calcium acetate monohydrate 2.11×10 -3 Part by weight (1.20×10 -5 mol) and Other than that, the same procedure as in Example 1-1 was carried out.
[0109] (Example 1-5) PC1-5 The raw materials were 33.96 parts by weight (0.232 mol) of ISB and 8.47 parts by weight of CHDM. Part by weight (0.059mol), PO3G1000 48.79 parts by weight (0.047mol ), DPC 72.35 parts by weight (0.338 mol), calcium acetate monohydrate 1.79 ×10 -3 Part by weight (1.01×10 -5 The same procedure as in Example 1-1 was carried out except that the amount of Ta.
[0110] (Example 1-6) PC1-6 The raw materials were 32.26 parts by weight (0.221 mol) of ISB and 10.77 parts by weight of BPA. Part by weight (0.047mol), PO3G1000 48.79 parts by weight (0.047mol ), DPC 68.06 parts by weight (0.318 mol), calcium acetate monohydrate 2.77 ×10 -3 Weight part (1.57×10 -5 mol) and the final polymerization temperature was 230°C. Other than that, the same procedure as in Example 1-1 was carried out.
[0111] (Comparative Example 1-1) The raw materials were 46.69 parts by weight (0.320 mol) of ISB and 43 parts by weight of PEG600. .07 parts by weight (0.074 mol), DPC 84.32 parts by weight (0.394 mol), Calcium acetate monohydrate 2.08 x 10 -3 Part by weight (1.18×10 -5 (mol) Other than that, the same procedure as in Example 1-1 was carried out.
[0112] (Comparative Example 1-2) The raw materials were ISB 46.70 parts by weight (0.320 mol), PPG 600 43 .12 parts by weight (0.074 mol), DPC 83.93 parts by weight (0.394 mol), Calcium acetate monohydrate 2.07 x 10 -3 Part by weight (1.18×10 -5 (mol) Other than that, the same procedure as in Example 1-1 was carried out.
[0113] (Comparative Example 1-3) The raw materials were ISB 46.69 parts by weight (0.320 mol), PTMG650 4 3.28 parts by weight (0.066 mol), DPC 82.65 parts by weight (0.386 mol) , calcium acetate monohydrate 6.80 x 10 -3 Part by weight (3.86×10 -5 mol) Other than that, the same procedure as in Example 1-1 was carried out.
[0114] (Comparative Example 1-4) PC2-6 This was carried out by the method shown in Production Example 6 described below.
[0115] (Comparative Example 1-5) PC2-3 This was carried out by the method shown in Production Example 3 described below.
[0116] [Table 1]
[0117] (Production Example 1) PC2-1 A continuous polymerization facility consisting of three vertical agitation reactors, one horizontal agitation reactor, and a twin-screw extruder. The polymerization of polycarbonate resin was carried out using ISB and DPC. The ISB was 42.5 kg / hr and the DPC was 63.2 kg / hr (ISB / DPC molar ratio). The mixture was continuously fed to the first vertical stirred reactor at a flow rate of PC=1.000 / 1.015. In the polymerization catalyst, an aqueous solution of calcium acetate monohydrate was added to 1 mol of all dihydroxy compounds. The first vertical stirred reactor was added with 1.5 μmol of calcium acetate monohydrate. The internal temperature, internal pressure, and residence time of each reactor were as follows: First vertical stirred reactor: 19 0℃, 25kPa, 120min, 2nd vertical stirred reactor: 195℃, 10kPa, 90min, 3rd 3 Vertical stirred reactor: 205℃, 4kPa, 45min, 4th horizontal stirred reactor: 220℃, 0. The pressure was 1 to 1.0 kPa and the time was 120 minutes. The number average molecular weight of the obtained polycarbonate resin was 8. The internal pressure of the fourth horizontal stirred reactor was finely adjusted to keep the internal pressure within the range of 000 to 9000. The polycarbonate resin discharged from the fourth horizontal agitation reactor was vented in a molten state. The mixture was fed into a twin-screw extruder TEX30α (manufactured by Japan Steel Works, Ltd.). The extruder had three vacuum vent ports. In this step, the remaining low molecular weight components in the resin are removed by volatilization, and the first vent is also used. Phosphonic acid was used as a catalyst deactivator in front of the polycarbonate resin at 0.64 wt pp m was added, and Irganox1010 and AS2112 were added to the polycarbonate just before the third vent. The resin was added at 1000 ppm by weight and 500 ppm by weight, respectively. The filtered polycarbonate resin is then passed through a 10μm Ultiple filter while still in the molten state. The mixture was passed through a two-candle filter (PALL) to filter out foreign matter. Polycarbonate resin is extruded in strand form from the mold, cooled with water, solidified, and then cut with a rotary cutter. The pelletized polycarbonate thus obtained was cut into pellets. The carbonate resin is referred to as "PC2-1." The results of the various evaluations mentioned above are shown in Table 2.
[0118] (Manufacturing Example 2) PC2-2 In addition to the raw materials used in Production Example 1, CHDM was also melted in a tank and the raw materials were charged. ISB 38.3kg / hr, CHDM 4.19kg / hr, DPC 62.9kg / hr hr (molar ratio ISB / CHDM / DPC = 0.900 / 0.100 / 1.010) The same procedure as in Production Example 1 was repeated except that the amounts were changed.
[0119] (Manufacturing Example 3) PC2-3 Raw material feeding: ISB 29.8kg / hr, CHDM 12.6kg / hr, DPC 62.9 kg / hr (molar ratio ISB / CHDM / DPC = 0.700 / 0.300 / The same procedure was carried out as in Production Example 2, except that the flow rate was changed to 1.008).
[0120] (Manufacturing Example 4) PC2-4 Raw material feeding: ISB 21.3kg / hr, CHDM 21.1kg / hr, DPC 62.9 kg / hr (molar ratio ISB / CHDM / DPC = 0.500 / 0.500 / The same procedure was carried out as in Production Example 2, except that the flow rate was changed to 1.005).
[0121] (Manufacturing Example 5) PC2-5 Using the reaction equipment used in Example 1-1, the raw materials were charged in the following amounts: ISB 70.89 parts by weight ( 0.485mol), 1,3-PDO 12.6.30 parts by weight (0.162mol), D PC 138.54 parts by weight (0.647 mol), calcium acetate monohydrate 5.70 x 1 0 -4 Weight part (3.23×10 -6 The same procedure as in Example 1-1 was repeated except that the reaction mixture was changed to (mol).
[0122] (Production Example 6) PC2-6 The raw materials were ISB 70.47 parts by weight (0.482 mol), PO3G 500 1 6.18 parts by weight (0.031 mol), DPC 110.58 parts by weight (0.516 mol) ), calcium acetate monohydrate 9.05×10 -4 Weight part (5.14×10 -6 mol) and Other than that, the same procedure as in Example 1-1 was carried out.
[0123] (Manufacturing Example 7) PC2-7 The raw materials were ISB 75.56 parts by weight (0.517 mol), PO3G 500 1 0.47 parts by weight (0.020 mol), DPC 115.70 parts by weight (0.540 mol) ), calcium acetate monohydrate 2.84 × 10 -4 Part by weight (1.61×10 -6 mol) and Other than that, the same procedure as in Example 1-1 was carried out.
[0124] [Table 2]
[0125] (Example 2-1) 50 parts by weight of the polycarbonate resin PC1-1 pellets obtained in Example 1-1 and Blended with 950 parts by weight of the polycarbonate resin PC2-3 pellets obtained in Example 3. After that, a twin-screw extruder TEX30HSS (manufactured by Japan Steel Works) equipped with a vacuum vent was used to extrude the mixture. The mixture was extruded at a cylinder temperature of 240°C and an extrusion rate of 12 kg / hr to obtain polycarbonate. The resulting polycarbonate resin composition was pelletized. Various evaluations were carried out, and the results are shown in Table 3.
[0126] (Examples 2-2 to 2-15) The same procedure as in Example 2-1 was carried out except that the composition was changed to that shown in Table 3.
[0127] (Comparative Examples 2-1 to 2-8) The polycarbonate resins obtained in Production Examples 1 to 7 were subjected to the above-mentioned various evaluations. was carried out.
[0128] [Table 3]
Claims
1. A polycarbonate resin containing at least a structural unit represented by formula (1) and a structural unit represented by formula (2), the polycarbonate resin containing 10% by weight or more and 70% by weight or less of the structural unit represented by formula (1) and 30% by weight or more and 80% by weight or less of the structural unit represented by formula (2). 【Chemistry 1】 【Chemistry 2】 (In formula (2), the average value of n is 3 or more and 45 or less.)
2. The polycarbonate resin described in claim 1, wherein the number average molecular weight of the structural unit represented by the formula (2) is 200 or more and 2,500 or less.
3. 1 3. The polycarbonate resin according to claim 1, having a number average molecular weight of 15,000 or more and 50,000 or less as calculated by H-NMR analysis.
4. A polycarbonate resin composition comprising the polycarbonate resin according to any one of claims 1 to 3 (a first polycarbonate resin) and a polycarbonate resin (a second polycarbonate resin) which contains at least a structural unit represented by the formula (1) and has a structure different from that of the first polycarbonate resin, The second polycarbonate resin contains 40% by weight or more and 90% by weight or less of the structural unit represented by the formula (1), A polycarbonate resin composition in which the weight ratio of the first polycarbonate resin to the second polycarbonate resin is 1 / 99 to 99 / 1.
5. The polycarbonate resin composition according to claim 4, wherein the second polycarbonate resin has a glass transition temperature of 90°C or higher and 200°C or lower.
6. 6. The polycarbonate resin composition according to claim 4, wherein the second polycarbonate resin contains a structural unit derived from an aliphatic dihydroxy compound or an alicyclic dihydroxy compound.
7. 7. The polycarbonate resin composition according to claim 4, comprising 0.01% by weight or more and 10% by weight or less of an acrylic resin containing 50% by weight or more of a structural unit represented by the following formula (3): 【Chemistry 3】 (In formula (3), R 1 R is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms which may have a substituent. 2 represents an aryl group which may have a substituent, or an aralkyl group which may have a substituent.
8. The polycarbonate resin composition according to any one of claims 4 to 7, further comprising 0.1 wt% or more and 10 wt% or less of polytrimethylene ether glycol having a number average molecular weight of 300 or more and 10,000 or less.
9. A method for producing the polycarbonate resin according to any one of claims 1 to 3, comprising a step of polycondensing a monomer raw material containing at least a dihydroxy compound forming a structural unit represented by formula (1), a dihydroxy compound forming a structural unit represented by formula (2), and a carbonate diester by transesterification, In the step, the dihydroxy compound forming the structural unit represented by the formula (2) is polytrimethylene ether glycol, and the number average molecular weight of the polytrimethylene ether glycol is 200 or more and 2,500 or less.
Citation Information
Patent Citations
Copolycarbonate
JP2011241277A
Methacrylic copolymer, method for producing the same, and methacrylic resin composition using the same
JP2011500914A
Polycarbonate resin composition for thin-walled optical component, and thin-walled optical component
JP2016125028A
Thermoplastic resin composition and molded article using the same
JP2017088774A
Interior and exterior member for automobile
JP2019019281A